Intrinsic Thermodynamics and Structures of 2, 4‐ and 3, 4‐Substituted Fluorinated Benzenesulfonamides Binding to Carbonic Anhydrases. (21st December 2016) - Zubrienė, Asta; Smirnov, Alexey; Dudutienė, Virginija; Timm, David D.; Matulienė, Jurgita; Michailovienė, Vilma; Zakšauskas, Audrius; Manakova, Elena; Gražulis, Saulius; Matulis, Daumantas
Abstract: The goal of rational drug design is to understand structure–thermodynamics correlations in order to predict the chemical structure of a drug that would exhibit excellent affinity and selectivity for a target protein. In this study we explored the contribution of added functionalities of benzenesulfonamide inhibitors to the intrinsic binding affinity, enthalpy, and entropy for recombinant human carbonic anhydrases (CA) CA I, CA II, CA VII, CA IX, CA XII, and CA XIII. The binding enthalpies of compounds possessing similar chemical structures and affinities were found to be very different, spanning a range from −90 to +10 kJ mol −1, and are compensated by a similar opposing entropy contribution. The intrinsic parameters of binding were determined by subtracting the linked protonation reactions. The sulfonamide group p K a values of the compounds were measured spectrophotometrically, and the protonation enthalpies were measured by isothermal titration calorimetry (ITC). Herein we describe the development of meta ‐ or ortho ‐substituted fluorinated benzenesulfonamides toward the highly potent compound10 h, which exhibits an observed dissociation constant value of 43 pm and an intrinsic dissociation constant value of 1.1 pm toward CA IX, an anticancer target that is highly overexpressed in various tumors. Fluorescence thermal shift assays, ITC, and X‐ray crystallography were all applied in this work. Abstract : Reasons for affinity : The correlations between chemical structure and thermodynamics of binding are described for an extremely high intrinsic affinity (dissociation constant down to 1.1 pm ) compound interaction with carbonic anhydrase IX, an anticancer drug target. The crystal structures of selected compounds bound to several carbonic anhydrase isoforms are also discussed.